Problems of Communicating Through the English Language in Tanzanian Universities - Shumbusho, George N. (Advances in Social Sciences Research Journal, 2020)
The paper begins with a brief overview of authors who have researched the problems caused by the English language when used as the Medium of Teaching and Learning in a context where it is not spoken as the first language. The paper agrees with authors’ findings and conclusions that indeed the English problems as the Medium of Teaching and Learning in Tanzania tertiary institutions and universities have increasingly become glaring and insurmountable under the prevailing curriculum of these institutions whereby grammar is not infused in English for Academic Purposes (EAP) syllabi of these institutions or universities. To testify the preceding allegation, the paper presents ample examples of bad English from various students’ writing from three universities in Tanzania. Three recommendations to alleviate the problem have been suggested. First, the infusion of grammar aspect into EAP syllabi; second, universities to have an adequate number of EAP lectures to cater for the needs of all students; third, students be encourage to read various books and academic journals to enable them to acquire a variety of genres and academic registers. On switching the Medium of Teaching and Learning from English to Kiswahili, the Tanzanian government should take a bold decision to switch now, otherwise it will never happen.